PEMANFAATAN LAHAN PRIBADI SEBAGAI LUMBUNG OBAT DI ERA PANDEMI BAGI WARGA KELURAHAN BELIAN - Isnaini Nuzula Agustin; Vivian Vivian; Winda Lius; Sherina Yoren; Michell Phang; Novita Chris; Audrey Saudjhana; Hans Yonathan; Willyana Willyana (National Conference for Community Service Project (NaCosPro), 2020)
The Coronavirus that has attacked Indonesia since last March affected the high needs for medicine, as an effort to increase immunities. On the other hand, the significant decline of economic conditions economically led to a lower purchasing power, compounded by increasing the price of goods in the market. One of the areas affected by COVID 19 in Batam is RT 004 Kelurahan Belian, where several residents had been infected with this virus. This community service activity aims to increase the community's knowledge of RT 004 Kelurahan Belian about cultivating pharmacy plants, thus they able to produce their own medicines by cultivating medicinal plants around their home environment. This activity is carried out in three stages, namely gathering initial information about medicinal plants, making video and poster campaigns, and ended by distributing and socializing through social media pages. Based on the results of extracting information, pharmacy plants that can be used as medicine and easy to grow are ginger, turmeric, lemongrass, cinnamon, aloe vera, and betel leaf. The videos and posters that are compiled contain the benefits of each plant's easy way to plant them. Furthermore, socialization is carried out online through social media so that the community, especially partners, can take advantage of this activity.